Optical sensors for monitoring dynamic changes of intracellular metabolite levels in mammalian cells - Hou, Bi-Huei; Großmann, Guido (Nature protocols, 2011)
Knowledge of the in vivo levels, distribution and flux of ions and metabolites is crucial to our understanding of physiology in both healthy and diseased states. The quantitative analysis of the dynamics of ions and metabolites with subcellular resolution in vivo poses a major challenge for the analysis of metabolic processes. Genetically encoded Förster resonance energy transfer (FRET) sensors can be used for real-time in vivo detection of metabolites. FRET sensor proteins, for example, for glucose, can be targeted genetically to any cellular compartment, or even to subdomains (e.g., a membrane surface), by adding signal sequences or fusing the sensors to specific proteins. The sensors can be used for analyses in individual mammalian cells in culture, in tissue slices and in intact organisms. Applications include gene discovery, high-throughput drug screens or systematic analysis of regulatory networks affecting uptake, efflux and metabolism. Quantitative analyses obtained with the help of FRET sensors for glucose or other ions and metabolites provide valuable data for modeling of flux. Here we provide a detailed protocol for monitoring glucose levels in the cytosol of mammalian cell cultures through the use of FRET glucose sensors; moreover, the protocol can be used for other ions and metabolites and for analyses in other organisms, as has been successfully demonstrated in bacteria, yeast and even intact plants. The whole procedure typically takes ~4 d including seeding and transfection of mammalian cells; the FRET-based analysis of transfected cells takes ~5 h.